Direct Vapor-Phase Bromination of Multiwall Carbon Nanotubes. (22nd May 2012) - Mazov, Ilya; Krasnikov, Dmitry; Stadnichenko, Andrey; Kuznetsov, Vladimir; Romanenko, Anatoly; Anikeeva, Olga; Tkachev, Evgeniy
Abstract : We present the simple procedure of the vapor-phase bromination of multiwall carbon nanotubes (MWNTs) at moderate temperatures. MWNTs with average diameter 9 ± 3 nm were treated with Br2 vapors at 250 ° C to produce Br-functionalized product. Transmission electron microscopy analysis was used to prove low damage of MWNT walls during bromination. X-ray photoelectron spectroscopy (XPS) and differential thermal analysis (DTA) were used to investigate chemical composition of the surface of initial and brominated nanotubes. The experimental results show that the structure of MWNTs is not affected by the bromination process and the total amount of Br-containing surface functions reaches 2.5 wt. %. Electrophysical properties of initial and brominated MWNTs were investigated showing decrease of conductivity for functionalized sample. Possible mechanism of the vapor-phase bromination via surface defects and oxygen-containing functional groups was proposed according to data obtained. Additional experiments with bromination of annealed low-defected MWNTs were performed giving Br content a low as 0.75 wt. % proving this hypothesis.